Radiological accuracy of two different systems (Digital & Conventional) in endodontic apical fitness (Mustansiria Dental Journal, 2018)
Aim: The present study compares the accuracy of conventional and digitalradiographic system in the determination of apical fitness in endodontic therapy.Method: Thirty three root canals of first upper and lower molar teeth were used inthis study; a K-file was inserted into the canal until its tip was fit snuggly onemillimeter shorter than the apex. Each tooth was radiographed twice with twodifferent radiographic systems; conventional & digital systems. The right-angleparalleling technique with film holders was used in both systems. The distancebetween the file tip and the center of radiographical apex from both imaging systemswas measured by two examiners and the mean of each two measurements wasrecorded, the data was collected and analyzed statistically by paired t- test.Results: The mean value of radiographic length reveals that there is a very smalldifference between the measurements of conventional radiographic system(0.8727mm) and those measurements of digital radiographic system (0.8367mm)when compared with the real length measurements (1mm). Paired t-test showsthat there is no significant difference (p < 0.05) was founded between the realmeasurements and the radiographic measurements are taken from both conventionaland digital systems. In conclusion both the conventional and digital imaging systemscan be used accurately for working length determination in an endodontic therapy.